2023
DOI: 10.1037/cdp0000509
|View full text |Cite
|
Sign up to set email alerts
|

Social identity threat across group status: Links to psychological well-being and intergroup bias through collective narcissism and ingroup satisfaction.

Abstract: Objectives. Through two correlational studies (Study 1: Turkish majority, Kurdish minority; Study 2: White British majority; Black minority), we examined the implications of social identity threat for majority and minority ethnic group members' psychological well-being and intergroup bias, using a social identity framework that incorporates the recently highlighted distinction between narcissistic and non-narcissistic positive evaluation of the ingroup (i.e., collective narcissism and ingroup satisfaction, res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
19
1

Year Published

2024
2024
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 82 publications
1
19
1
Order By: Relevance
“…Just as narcissism is qualitatively different from and has a different etiology than self-esteem (Brummelman, Thomaes, & Sedikides, 2016), collective narcissism is a distinct and separate phenomenon from ingroup satisfaction (Golec de Zavala et al, 2019;2020;. They are, as Golec de Zavala and colleagues (2020) argue 'alternative beliefs that people may hold about the social identities they share' (p. 742) Individuals who endorse collective narcissism are sensitive to threats to the perceived greatness of the ingroup (Bagci et al, 2021;Guerra et al, 2020). When the ingroup does not receive the admiration it is believed to deserve, collective narcissists react with hostility, retaliatory aggression, and joy at the misfortunes of outgroups in both observational and experimental studies (Golec de Zavala et al, 2009;Golec de Zavala, Cichocka, & Iskra-Golec, 2013b;Golec de Zavala, Pekker, Guerra, & Baran, 2016;Hase et al, 2021).…”
Section: Collective Narcissism Ingroup Satisfaction and Nationalismmentioning
confidence: 99%
“…Just as narcissism is qualitatively different from and has a different etiology than self-esteem (Brummelman, Thomaes, & Sedikides, 2016), collective narcissism is a distinct and separate phenomenon from ingroup satisfaction (Golec de Zavala et al, 2019;2020;. They are, as Golec de Zavala and colleagues (2020) argue 'alternative beliefs that people may hold about the social identities they share' (p. 742) Individuals who endorse collective narcissism are sensitive to threats to the perceived greatness of the ingroup (Bagci et al, 2021;Guerra et al, 2020). When the ingroup does not receive the admiration it is believed to deserve, collective narcissists react with hostility, retaliatory aggression, and joy at the misfortunes of outgroups in both observational and experimental studies (Golec de Zavala et al, 2009;Golec de Zavala, Cichocka, & Iskra-Golec, 2013b;Golec de Zavala, Pekker, Guerra, & Baran, 2016;Hase et al, 2021).…”
Section: Collective Narcissism Ingroup Satisfaction and Nationalismmentioning
confidence: 99%
“…When it becomes a prevalent way of defining the ingroup's identity, it is likely to undermine group members' wellbeing. Indeed, collective narcissism is associated with chronically low life satisfaction, predominantly negative mood and negative emotionality (Golec de Zavala, 2019;Golec de Zavala et al, 2022), and, unlike non-narcissistic ingroup satisfaction, it does not predict well-being in advantaged or disadvantaged groups (Bagci et al, 2021). Thus, to understand the role of ingroup identification in the context of intergroup exclusion, it is important to examine not only whether group members identify with the excluded ingroup, but also how they identify with it, as ingroup identification is a multifaceted phenomenon (e.g., Leach et al, 2008).…”
Section: Gender Collective Narcissism and Parochial Vicarious Ostracismmentioning
confidence: 99%
“…Collective narcissism is an aspect of ingroup identification that pertains to positive evaluations of the ingroup (Golec de Zavala et al, 2009. However, unlike nonnarcissistic positive regard for the ingroup (e.g., private collective self-esteem, Crocker & Luhtanen, 1990;ingroup satisfaction, Leach et al, 2008;positive ingroup regard, Brewer, 2011), collective narcissism is chronically associated with exaggerated perceptions of intergroup threat, conflict, and injustice against the ingroup, regardless of the ingroup's actual situation (Bagci et al, 2021;Golec de Zavala et al, 2016Guerra et al, 2022;Hase et al, 2021).…”
Section: Gender Collective Narcissism and Parochial Vicarious Ostracismmentioning
confidence: 99%
“…Some of the most striking evidence of the role of identity comes from studies exploring the relationship between conspiratorial beliefs and collective narcissism. Collective narcissism is the belief that one's group is not recognized for their inherent greatness (Golec De Zavala et al, 2009) and has been consistently associated with social identity threat (Bagci et al, 2021) and conspiracy theory beliefs (Golec de Zavala & Cichocka, 2012;Sternisko et al, 2021;Marchlewska et al, 2019). For instance, a recent international study across 56 countries found that people with higher collective narcissism were much more likely to believe a variety of conspiracy theories about COVID-19 (Sternisko et al, 2021).…”
Section: Evidencementioning
confidence: 99%